Best Proximity Point Results for Quasi Contractions of Perov Type in Non-Normal Cone Metric Space - Hussain, Azhar; Abbas, Mujahid; Ahmad, Jamshaid; Al-Mazrooei, Abdullah Eqal (Communications in Mathematics and Applications, 2019)
In this paper, we study the notion of Ciric-Perov quasi contraction and Fisher-Perov quasi contraction and prove some best proximity point theorems for such contractions in the frame work of non-normal regular cone metric spaces. We give an example to support our result. Our results extend and generalized many existing results in literature.